USING THE APPLIED BEHAVIOR ANALYSIS TECHNIQUE IN DEALING WITH THE SYMPTOMS OF AUTISM SPECTRUM DISORDER TO DEVELOP NEW ABILITIES - Sultan , Nargiz (Collection of scientific papers «ΛΌГOΣ», 2022)
The Denver model of Early Intervention is considered to be one of the existing and successfully applied practices of complex therapy. This model is based on the norms of the ABA (Applied Behavior Analysis). The use of the ABA technique in dealing with the symptoms of ASD (Autism Spectrum Disorder) provides for the possibility of changing the behavior manifested through the development of communication and other skills. So, the intervention of ABA can be aimed at developing new abilities or minimizing undesirable behavior that interferes with the development of the child and his socio-psychological adaptation. More and more evidence indicates that intervention carried out by trained parents can be an important part of a therapeutic program aimed at socio-psychological adaptation [8, p.162]. What is commonly referred to as “parent education” in this case is divided into 2 categories: parental support and parental intervention. The support of parents is aimed at obtaining the necessary minimum of knowledge and brings indirect benefits to the child. It includes the coordination of care and psychological education. The method of “therapy by the hands of parents”, in which dad and mom master the techniques of helping a child, can be used in dealing with the main symptoms of ASD or other behavioral manifestations.